Fabrication And Characterization Of Gum Arabic Bonded Rhizophora spp. Particleboard Head Phantom For Pet/Ct Applications - Abuarra, Ali Mohammad Hamdan (2014)
Gum Arabic was used to manufacture Rhizophora spp. particleboards with three particle sizes (149 - 210 μm, 74 - 149 μm, and < 74 μm) at four different GA adhesive levels (0%, 5%, 10%, and 15%). The density, moisture content (MC), internal bond (IB) strength, thickness swelling (TS), water absorption (WA), CHNS (carbon, hydrogen, nitrogen, and sulfur), structural morphology and the mass attenuation coefficient measurements were used to characterize the fabricated particleboards. Gam Arab telah ditambah ke dalam papan serpai Rhizophora spp. dengan tiga saiz zarah (149 - 210 μm, 74 - 149 μm, dan < 74 μm ). Pada empat tahap perekat GA yang berbeza (0%, 5 %, 10 %, dan 15%). Ketumpatan, kandungan lembapan (MC), kekuatan ikatan dalaman (IB), bengkak ketebalan (TS), penyerapan air (WA), CHNS (karbon, hidrogen, nitrogen, dan sulfur), morfologi struktur dan peng ukuran pekali atenuasi tisu telah digunakan untuk mencirikan papan serpai yang dihasilkan.